2017
DOI: 10.1111/cen.13394
|View full text |Cite
|
Sign up to set email alerts
|

The Turner syndrome life course project: Karyotype‐phenotype analyses across the lifespan

Abstract: Karyotype may play an important factor against stratifying risk of comorbidity in TS and should be taken into consideration when managing adults with TS. Further investigations of the isochromosome (Xq) and ring groups are necessary to further clarify their associations with comorbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
104
1
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(116 citation statements)
references
References 16 publications
7
104
1
4
Order By: Relevance
“…It is due to the absence or structural abnormality of one of the X chromosome, with various degrees of mosaicism. Mosaicism attenuates the phenotype of Turner syndrome, especially the anthropometric data and the cardio-vascular morbidities [5,6]. Diagnosis of mosaic forms is established 8 years after the monosomic ones [7].…”
Section: Introductionmentioning
confidence: 99%
“…It is due to the absence or structural abnormality of one of the X chromosome, with various degrees of mosaicism. Mosaicism attenuates the phenotype of Turner syndrome, especially the anthropometric data and the cardio-vascular morbidities [5,6]. Diagnosis of mosaic forms is established 8 years after the monosomic ones [7].…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Previous studies investigating elevated LFTs and autoimmunity have yielded controversial results. 4,5,13,14 Recently, an association between higher alanine aminotransferase (ALT) levels and ring X karyotype was found in a large TS population, 15 whereas prior studies had shown no association with TS-karyotypes. Finally, cohort studies have suggested that the architectural liver changes described in TS may be the consequence of a primary vascular derangement.…”
mentioning
confidence: 99%
“…Indeed two additional previously known Turner syndrome cases were not detected by the SNP array method because they had loss of Xp and gain of Xq making the overall X chromosome dosage not significantly different from normal 46,XX. We suspect that these are isochromosomes, which contribute to about 15% of Turner syndrome cases in other published series 18,26 . We adapted our protocol to find additional cases with non-aneuploid X chromosome abnormalities and found a total of 5 cases of suspected 46X, i(Xq) and 9 with X chromosome deletions, although we were not able to validate these findings with an independent technology.…”
Section: Syndromementioning
confidence: 86%
“…The majority of these women were mosaic. The published prevalence of Turner syndrome is 1/2,500, however only approximately 60% of those Turner syndrome cases are caused by 45,X or 45,X/46,XX mosaicism, the rest being due to other abnormalities such as deletions or isoXq 13,18 , thus the prevalence of aneuploidy causing Turner syndrome is around 1/4,200.…”
Section: Prevalence Of X Chromosome Aneuploidymentioning
confidence: 99%